Menempatkan Masyarakat Pada Posisi Sentral Dalam Proses Pembangunan - Soetomo, - (Jurnal Ilmu Sosial dan Ilmu Politik, 1998)
The UNESCO defines the goals, objectives and the aims of development to be: not to develop things but to develop men. It means that the development process has to emphasize to promote the capacity of human resources and institutions in each community. Therefore in that process, community initiative and capacity in local level are very important. Nevertheless, governmental or non-governmental organization can execute some programs as an intervention in that process. In order that intervention has an impact to increase the capacity of the people, it has to use a principle; help the people to help themselves or intervention is a part of enabling process.